Avaliação da qualidade das ementas em instituições particulares de solidariedade social do Concelho de Águeda - Lima, João (2013)
Introduction: The qualitative assessment of menus lets enables the knowledge about the conformity of meals with the recommendations for healthy eating. Objectives: To evaluate qualitatively the menus of four charities of the county of Águeda, identifying the major non- -conformities, envisaging intervention solutions. Methodology: After collection of menu plans, they were qualitatively analyzed using the criteria listed in the System of Planning and Evaluation of School Meals. Results: 50% of the menus were classified as unacceptable and 50% were acceptable. In general items 50% of the menus were classified as unacceptable and 50% were acceptable. All soups were classified as unacceptable. 75% of the menus were classified according to the quality of meat, fish and eggs offered as unacceptable, and 25% as acceptable. With regard to suppliers accompaniments of carbohydrates, 50% of the menus were classified as acceptable and the others as very good and the accompanying vegetables and legumes, 50% as acceptable and the other as unacceptable. Regarding dessert, 50% of the menus were acceptable, 25% unacceptable and 25% very good. Discussion: Faults found eventually compromise the main objectives of food education in schools, which should go through the children create positive attitudes to food and diet, develop healthy eating habits and highlight the need for a healthy and diversified promotion health. Conclusions: This study shows the need for improving nonconformities, namely through the action of skilled health professionals to incorporate the provision of meals